Czech version of a conceptual framework for the topic nervous system and representation of its concepts in secondary school textbooks - Janštová, Vanda; Spurný, Jakub; Procházková, Kamila (Scientia in educatione, 2024)
We present the Czech version of the conceptual framework of the nervous system for the secondary school level. The original framework was developed as a result of a Delphi study led by P˚al Kvello (2021). The Czech version was prepared according to the TRAPD method. The representation of each concept in nine biology textbooks was analysed. Concepts describing the anatomy of the nervous system were the ones most frequently represented, concepts primarily related to physiology were typically partially included, and concepts describing the connections with behaviour, learning, perception, feelings, and experiences of the individual were typically missing. On the contrary, some facts that do not contribute to an understanding of the principles but rather indicate that the teaching texts reflect a state of knowledge that is many decades old were represented across the texts. Therefore, the Czech secondary school biology textbooks do not reflect the current state of knowledge and recommendations for the selection of content taught. The translation of the conceptual framework can serve as an inspiration for the selection of professional content on the nervous system at the secondary school level and a basis for the development of teaching materials by professionals and teachers in the Czech context.